Non-Surgical Repair of Internal Resorption with MTA: A Case Report - Mohammadi, Zahed; Yazdizadeh, Mohammad; Shalavi, Sousan (Iranian Endodontic Journal, 2012)
Internal resorption is rare in permanent teeth. Treatment is usually performed through warm gutta-percha technique. If the resorptive process perforates the root, treatment may be more difficult and is usually performed via surgical approach. Non-surgical repair of a perforating internal root resorption with MTA was conducted in this case. Before repairing the resorption, a master gutta-percha point was placed in the canal to maintain negotiability of the original canal path. Then, MTA was prepared and applied with a small carrier in the resorption area and compacted. Thereafter gutta-percha was retrieved and the access cavity was closed with a temporary filling material. In the second visit, the root canal was obturated with gutta-percha and AH26 sealer using lateral compaction technique and subsequently, the crown was restored. The symptoms and signs ceased and the result was satisfactory at the 18 month follow-up visit.